The networked nonprofit connecting with social media to drive change - Kanter, Beth, 1957- (Jossey-Bass, 2010)
"This groundbreaking resource offers a set of guiding principles to help nonprofit leaders navigate the transition from top-down organizations to a networked approach enabled by technology. The book contains specific strategies for implementation and secrets to success from nonprofits who have used new social media tools effectively themselves. It also offers effective exercises and how-to's for implementation. A key element of this book is interviews with current nonprofit managers who have learned how to jump into the social media fray without a net and thrived because of it"--